Effect of Different Drying Temperatures on the Physicochemical Properties of Sago Starch-Bacterial Cellulose Film Incorporated with Gunuang Omeh Orange Essential Oil - Maulana Yuda Anantama; Fadli Hafizulhaq; Andasuryani Andasuryani (Green Engineering Society, 2026)
Extensive and irresponsible use of conventional plastic has brought serious problems to the planet due to its low biodegradability. In order to reduce the risks, packaging materials made from biodegradable materials are extremely needed. This study develops active packaging films using sago starch and bacterial cellulose incorporated with Gunuang Omeh orange peel essential oil. It also evaluated the effect of different drying temperatures on the physicochemical, mechanical, structural, and antimicrobial properties of the resulting films. The solvent casting method was used to prepare sample films with 3 drying temperatures (40, 45, and 50°C). The functional properties and antibacterial activity against E. coli and S. aureus of films with and without essential oil were characterized and analyzed. The results showed that drying temperature significantly influences the performance of the biofilms. Higher tensile strength (2.38 MPa) and lower moisture absorption were found at 45°C dried films. The presence of essential oil slightly increased water solubility and improved antibacterial activity, with inhibition zones ranging from 7.70–15.77 mm against E. coli and 4.83–5.75 mm against S. aureus. In conclusion, sago starch–bacterial cellulose films incorporated with Gunuang Omeh orange essential oil demonstrate a future potential as eco-friendly packaging materials, with drying temperature identified as a critical processing parameter for optimizing functional performance.